The Influence of Bantengan on Gender Roles, Social Inclusion, and The Formation of Children's Identities in Tumpang District - Pratama, Ariel Athahudan (PSGA Institut Agama Islam Tarbiyatut Tholabah, 2023)
Bantengan, a traditional art from Indonesia, blends martial arts, dance, music, and theater. Historically linked to martial arts, Bantengan preserves culture and addresses gender, inclusion, and child development issues. It shapes gender identity by reinforcing traditional values and promoting inclusivity but faces challenges such as restrictive norms and trance-related risks. Bantengan fosters social inclusion by encouraging empathy, cooperation, and interaction while supporting local economies through performance-related trade. For children, it serves as an educational platform to instill cultural knowledge, creativity, and character. However, risks like exposure to violence and neglect of academic pursuits need attention. A balanced, inclusive approach ensures Bantengan remains a valuable cultural and social asset.